Impact of hydration on muscle contraction properties of elite competitive wrestlers - Garcia, J. M.; Calvo, B.; Monteiro, L.; Massuca, L.; Portillo, J.; Abian-Vicen, J. (Archives of Budo, 2016)
Background and Study Aim: The wrestling events included in the Olympic Games have different weight classes. Most wrestlers reduce their body weight a few days before competition so they can enter the right weight category. Often they use irrational nutritional strategies to make the weight, sometimes even drastically reducing their water intake. The purpose of this study was the knowledge about influence of pre-competition level of hydration on muscle contractile properties in elite wrestlers.